2018
DOI: 10.1007/s10943-018-0676-1
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the Personal Values of the University Students in Different Departments

Abstract: This research aims to examine the personal values of the first-year university students studying in different departments. This is a descriptive cross-sectional survey study. Research population is composed of first-grade students approving to participate and studying in the Nursing Department in the School of Health, Biology Department in the Faculty of Science and Letters and the Department of Early Childhood Education in the Faculty of Education of Uludağ University. "Student Information Form" and "Schwartz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Racko et al (2017) found an increase in power and hedonism values in a 2-year longitudinal study of economics students. Tunç et al (2020) found that the power, achievement and hedonism value scores of the students in the nursing department of health sciences were higher, compared to the students in the departments of science and educational sciences. Krishnan (2008) demonstrated that management education enhanced the importance of selforiented values and reduced the importance of others-oriented values.…”
Section: Change In Value Systemsmentioning
confidence: 89%
See 1 more Smart Citation
“…Racko et al (2017) found an increase in power and hedonism values in a 2-year longitudinal study of economics students. Tunç et al (2020) found that the power, achievement and hedonism value scores of the students in the nursing department of health sciences were higher, compared to the students in the departments of science and educational sciences. Krishnan (2008) demonstrated that management education enhanced the importance of selforiented values and reduced the importance of others-oriented values.…”
Section: Change In Value Systemsmentioning
confidence: 89%
“…Schwartz and Rubel (2005) found that men attributed consistently more importance than women did to power, stimulation, hedonism, achievement and self-direction values. Tunç et al (2020) demonstrated that the value scores of female students for hedonism, universalism, benevolence and conformity were higher than those of male students, while the achievement scores were higher among male students. Goodwin et al (2020) found that women, compared to men, expected a lower sense of power when considering applying to a majority-male leadership committee.…”
Section: Gm 371mentioning
confidence: 93%